Effects of honey consumption on bone metabolism in female athletes / Nur Syamsina Ahmad - Nur Syamsina , Ahmad (2017)
Reproductive hormone disturbances, diet restriction and minimal involvement in weight bearing exercises are some of various risk factors for low bone mass density (BMD) in female athletes. Honey has been scientifically proven to prevent bone loss, improve estrogen secretion and reduce oxidative stress but limited to studies conducted on rats. It is inconclusive whether honey supplementation would have the same benefit in humans, especially female athletes. First study aimed to assess the association between BMD and energy availability, body composition, estrogen level and bone loading status in female athletes and to what extend those factors predict BMD. Body composition, BMD, energy intake, energy expenditure, Bone Physical Activity Questionnaire (BPAQ) score and estrogen level were determined from 85 female athletes aged 18–29 years. Results showed that 53% of female athletes had low BMD and the mean (SD) of energy intake was 1291 (33) kcal/day. BMD was positively associated (p<0.05) with BPAQ score and body weight but negatively associated (p<0.05) with energy expenditure. There was no association between estrogen, energy intake and energy availability with BMD. Energy expenditure and BPAQ score were the main factors that contributed to low BMD in female athletes. Second study was to investigate the acute effects of high and low Tualang honey (TH) dosages on antioxidant activity and oxidative stress. 20 female athletes were assigned equally into low honey (LH) and high honey (HH) dosage group. Blood was collected before (0 hours) and after 0.5, 1, 2 and 3 hours honey ingestion to determine Total phenolic content (TPC), Ferric reducing antioxidant power (FRAP), Malondialdehyde (MDA) and Reactive oxidative species (ROS). Both LH and HH groups increased antioxidant activity and reduced oxidative stress and no difference found between groups. The third study was to determine whether BMD, bone metabolism, estrogen levels, and oxidative stress are influenced by the consumption of TH or a combination of TH and jumping exercise for 8 weeks in female athletes. Forty-five female athletes with low BMD were equally assigned into three groups: honey (H), honey combined with jumping (HJ) and jumping (C). BMD was measured, and blood was analyzed for estrogen level, bone biomarkers [Bone Alkaline Phosphatase (BAP), C-terminal telopeptides type 1 collagen (ICTP)] and oxidative stress biomarkers (MDA and ROS) pre- and post- intervention. After 8 weeks, H and HJ showed an improvement in BMD score, estrogen levels and bone biomarkers but no significant difference were observed between the three groups. MDA and ROS values were significantly reduced (p<0.05) in H and HJ but were significantly increased in C. In comparison to C, H and HJ were significantly lower (p<0.05) for ROS but not MDA. In conclusion, low BMD in female athletes is associated with high energy expenditure and poor mechanical bone loading. To counter these conditions, TH intake for 8 weeks or combined with jumping exercise were found to be an alternative treatment for female athletes with low BMD as it appeared to improve estrogen levels and have preventive effects towards bone loss and oxidative stress.